Gas–liquid mass transfer characteristics of aviation fuel scrubbing in an aircraft fuel tank - Li Chaoyue (Nature Portfolio, 2021)
Abstract Dissolved oxygen evolving from aviation fuel leads to an increase in the oxygen concentration in an inert aircraft fuel tank ullage that may increase the flammability of the tank. Aviation fuel scrubbing with nitrogen-enriched air (NEA) can largely reduce the amount of dissolved oxygen and counteract the adverse effect of oxygen evolution. The gas–liquid mass transfer characteristics of aviation fuel scrubbing are investigated using the computational fluid dynamics method, which is verified experimentally. The effects of the NEA bubble diameter, NEA superficial velocity and fuel load on oxygen transfer between NEA and aviation fuel are discussed. Findings from this work indicate that the descent rate of the average dissolved oxygen concentration, gas holdup distribution and volumetric mass transfer coefficient increase with increasing NEA superficial velocity but decrease with increasing bubble diameter and fuel load. When the bubble diameter varies from 1 to 4 mm, the maximum change of descent rate of dissolved oxygen concentration is 18.46%, the gas holdup is 8.73%, the oxygen volumetric mass transfer coefficient is 81.45%. When the NEA superficial velocities varies from 0.04 to 0.10 m/s, the maximum change of descent rate of dissolved oxygen concentration is 146.77%, the gas holdup is 77.14%, the oxygen volumetric mass transfer coefficient is 175.38%. When the fuel load varies from 35 to 80%, the maximum change of descent rate of dissolved oxygen concentration is 21.15%, the gas holdup is 49.54%, the oxygen volumetric mass transfer coefficient is 44.57%. These results provide a better understanding of the gas and liquid mass transfer characteristics of aviation fuel scrubbing in aircraft fuel tanks and can promote the optimal design of fuel scrubbing inerting systems.